Особливості розподілу лімфоцитів з рецепторами до лектину арахісу в структурах періодонту щурів в нормі та після внутрішньоутробної антигенної дії - Бурега, Юрій Олексійович; Burega, Yu. O. (My University, 2015)
З періоду новонародженості до 7-ї доби післянатального життя відмічається збільшення вмісту РМД+лімфоцитів. В групі антигенпремійованих тварин їх кількість достовірно вища порівняно з тваринами інтактної групи. з 11-ї до 14-ї доби післянатального розвитку у сполучній тканині періодонтального простору виявляється різке зменшення вмісту РИД+лімфоцитів у всіх групах тварин, але у вакцинпремійованих тварин кількість РИД+лімфоцитів залишається дещо вищою. до 45-ї доби життя тварин, включно, в періодонті, зберігається тенденція поступового зниження кількості лімфоцитів із залишками р-Р-галактози. Вміст РИД+лімфоцитів на момент закінчення експерименту в усіх групах щурів не відрізняється, та не перевищує показників фізіологічної норми. Lymphocytes is the main factor of morphogenesis. The change of lymphocytes’ receptor repertory, that inducing by antigenic action in the fetal period of formation, influence to the organs and development of organism tissues after birth. Disorders in the proliferation, differentiation and migration processes of lymphocytes after intrauterine injection of various nature antigens, leads to population of immunological immature PNA+lymphocytes in peripheral lymphoid organs. Functional activity of immunological immature PNA+lymphocytes inducing the change in functioning, imbalance in formation cells of microenvironment, synthesis of intracellular substance and the fibers of extracellular matrix, that leads to violation of organs’ morph-functional condition, generally. Objective. To determine the features of distribution of lymphocytes with to peanut agglutinin in periodontal structures of rats in norm and after intrauterine antigenic action. Methods. The object of the research was 224 jaws of 112 white laboratory rats. The rats divided into three groups. First group is intact rats. Second group is rats, which were introduced 0,05 ml solution of antigen in the amniotic fluid on the 18th day of pregnancy by the method of N. Voloshyn, the third group - control, the animals were introduced intrauterine 0,05 ml of physiological solution on the 18th day of pregnancy. For the study of peculiarities of PNA+lymphocytes content in the periodontal structures after antigen’s action on the fetus, chosen the model of transuterine, transmembrane introduction of antigen in amniotic waters by the method of N. Voloshyn. The antigen was rare (killed) split - vaccine Vaxigrip 2009. The animals’ killing and taking of the material done from 13-00 till 14-00 on the 1st, 5th, 7th, 11th, 14th, 30th, 45th day of postnatal life. For the investigation, the jaw specimens with in the area of the molars used during some minutes after killing. The sugar residues determination of p-D-galactose investigated using the standard method through peanut agglutinin (PNA) using the standard kit of NPVK “LectinTest”, Lviv. For visualization was used 3.3’-diaminobenzidine - hydrogen peroxide system as the staining agent. The PNA+lymphocytes quantities counted per notional area unit through A. Glagolev’s modified ocular grid with the findings recalculation per 5000 pm2 (1000 magnifications). Processing of the obtained numerical results conducted through statistical methods - STATISTICA® for Windows 6.1 (StatSoft Inc., № AXXR712D833214FAN5). The results were evaluated at the p<0,05 significance level.
Features of Distribution of Lymphocytes with Receptors to Peanuts Agglutinin in Periodontal Structures of Rats in Norm and after Intrauterine Antigenic Action
Keywords: періодонт; сполучна тканина; лімфоцит; лектин арахісу; щурі; periodontium; connective tissue; lymphocyte; peanut agglutinin; rat